2019
DOI: 10.1002/ptr.6299
|View full text |Cite
|
Sign up to set email alerts
|

Tectorigenin protects against experimental fulminant hepatic failure by regulating the TLR4/mitogen‐activated protein kinase and TLR4/nuclear factor‐κB pathways and autophagy

Abstract: Tectorigenin has received attention due to its antiproliferation, anti‐inflammatory, and antioxidant activities. In this study, we investigated the effects of tectorigenin on lipopolysaccharide (LPS)/D‐galactosamine(D‐GalN)‐induced fulminant hepatic failure (FHF) in mice and LPS‐stimulated macrophages (RAW 264.7 cells). Pretreatment with tectorigenin significantly reduced the serum levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST), histological injury, apoptosis, and the mortality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…48,49 It was reported that tectorigenin also decreased Toll-like receptor (TLR)-4 expression and inhibited the activation of MAPK and NF-κB pathways to attenuate liver injury. 48 Furthermore, daphnetin notably inhibited liver dysfunction in D-GalN/LPS-induced ALF models by down-regulating the levels of MDA, MPO, nitric oxide synthase (iNOS) and cyclooxygenase (COX)2 while up-regulating the levels of GSH and SOD. 49 In addition, mesenchymal stem cells (MSCs) and their derivatives are effective autophagy regulators in the inhibition of liver injury in- up-regulating the expression of the antioxidative stress factor HO-1 in mouse models.…”
Section: Modulation Of Autophagy Reduces Apapinduced Liver Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…48,49 It was reported that tectorigenin also decreased Toll-like receptor (TLR)-4 expression and inhibited the activation of MAPK and NF-κB pathways to attenuate liver injury. 48 Furthermore, daphnetin notably inhibited liver dysfunction in D-GalN/LPS-induced ALF models by down-regulating the levels of MDA, MPO, nitric oxide synthase (iNOS) and cyclooxygenase (COX)2 while up-regulating the levels of GSH and SOD. 49 In addition, mesenchymal stem cells (MSCs) and their derivatives are effective autophagy regulators in the inhibition of liver injury in- up-regulating the expression of the antioxidative stress factor HO-1 in mouse models.…”
Section: Modulation Of Autophagy Reduces Apapinduced Liver Injurymentioning
confidence: 99%
“…Intriguingly, several kinds of plant extracts that serve as effective antioxidant and anticancer agents have been proven to activate autophagy and reduce inflammation to inhibit the progression of D‐GalN/LPS‐induced liver injury. Treatment with tectorigenin or daphnetin protected against D‐GalN/LPS‐induced liver injury by activating autophagy and suppressing the secretion of inflammatory cytokines, including TNF‐α, IL‐6 and IL‐1β 48,49 . It was reported that tectorigenin also decreased Toll‐like receptor (TLR)‐4 expression and inhibited the activation of MAPK and NF‐κB pathways to attenuate liver injury 48 .…”
Section: Autophagy and Chemically Induced Ali In Animal Modelsmentioning
confidence: 99%
“…It has been reported that cyanidin-3-O-glucoside (C3G), one of the most abundant monomers in vaccinium oxycoccus pigment, improved hepatic steatosis in mice [ 21 , 22 ]. Furthermore, tectorigenin (TEC) was also one of the active ingredients of blueberries, which inhibited the expression of toll-like receptor-4 (TLR4) and the activation of the MAPK/NF-κB pathway to promote autophagy and protect liver failure [ 23 ]. These analysis emphasized the need to estimate the reasonable utility of blueberry monomer in NASH treatment and to research the mechanisms involved.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, the FDA have therapeutics consisting of approximately 49% of drugs derived from natural products or their derivatives from 1981 to 2014 (Newman & Cragg, 2016). Tectorigenin, a main component derived from Belamcanda chinensis, has proved to possess multiple pharmacological activities including antiinflammatory, antioxidant activities, and antiapoptosis activities (Wang et al, 2017; Wang, Jing, et al, 2020; Zhang, Zhao, et al, 2019). Of them, recent studies have also highlighted that tectorigenin is protected against diabetic nephropathy by mediating the expression of adiponectin receptor 1/2 and the antioxidant action (Lee et al, 2000; Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%